Sympathetic efferent neurons are less sensitive than nociceptors to 4 Hz sinusoidal stimulation - Jonas, Robin; Namer, Barbara; Schnakenberg, Mark; Soares, Sabrina; Pakalniskis, Julius; Carr, Richard; Schmelz, Martin; Rukwied, Roman (European Journal of Pain, 2020)
BACKGROUND: Sinusoidal current stimuli preferentially activate C-nociceptors. Sodium channel isoforms NaV1.7 and NaV1.8 have been implicated in this. Sympathetic efferent neurons lack NaV1.8 and were explored upon sinusoidal activation. METHODS: Quantitative Sudomotor Axon Reflex Test (QSART) was performed in hairy (n = 16) and glabrous (n = 12) skin. Responses of sympathetic efferents (n = 10) and nociceptive afferents (n = 21) to sinusoidal current stimulation (4 Hz, 0.05-0.15 mA) were recorded in humans by microneurography (n = 11). Activation of sympathetic units upon supra-threshold sinusoidal currents (>0.8 mA) was recorded in pigs (n = 8). RESULTS: Sinusoidal stimuli (4 Hz, 0.4 mA) evoked weak sweat output (30 ml/h/m2 ) in hairy skin compared to rectangular pulses (4 Hz, 5 mA, 53 ml/h/m2 , p < .00001, ANOVA). No change in sweat output was recorded from glabrous skin to sine wave stimuli. Sinusoidal current at intensities ranging from 0.05 to 0.15 mA activated almost all (85%) nociceptors but only 40% of sympathetic units in human. Stimuli lead to a significantly lower activation in sympathetic versus nociceptive fibres as measured by activity-dependent slowing (ADS) of conduction (sympathetic efferents average ADS 100 ± 0.2% vs. C-nociceptors average ADS 113 ± 4%, p < .003, ANOVA). CONCLUSIONS: Sympathetic efferent neurons are less apt to convert slow depolarizations into action potentials as compared to nociceptors. Distinctive sodium channel expression patterns between nociceptors and sympathetic efferent neurons may account for this difference. Sinusoidal stimulation therefore provokes weak sweat responses and provides no alternative for clinical assessment of autonomic function. SIGNIFICANCE: C-nociceptors in hairy skin are activated by 4 Hz sinusoidal current stimulation at lower intensities than myelinated fibres. Sympathetic efferent neurons-albeit also unmyelinated-are less responsive to sinusoidal activation than nociceptors within the same skin area. Cutaneous sympathetic efferent neurons apparently are less apt than nociceptors to convert slow depolarization into action potentials.
EVALuna2:213481